Ireland in the nineteenth century : a breviate of official publications - Maltby, Arthur; Maltby, Jean (Guide to official publications, 1979)
Ireland in the Nineteenth Century: A Breviate of Official Publications offers information on the compilation of documents regarding Ireland from the 1-000 Act of Union until the 1970's, covering subjects such as education, agriculture, poverty, finance, health, and transport. The book first focuses on government documents, including the Act of Union, parliamentary privilege, peerage, public offices and public works, local government areas, and grand jury presentments. The text also looks at documents in finance, ownership and valuation of land, agriculture, and poverty and health measures. Top.